DISCRIMINATORY POLICY OF THE INDONESIAN GOVERNMENT TOWARD ADVOCATE AND POOR PEOPLE, FUNDING SOLUTION FOR LEGAL AID - Raharjo, Agus (Indonesian Journal of International Law, 2016)
Constitutionally, obtaining legal aid for the poor is a right, whereas for advocates, legal aid is an obligation. The rich can select the desired advocate, while the poor should be defended by an advocate under the principle of pro bono publico. Legal aid for the poor is the answer to the principle of equality before the law. Although the poor have a right to be defended by an advocate, some of them do not get legal aid, due to either the factor of the advocate or the poor themselves who do not have access to justice. Government policy to allocate legal aid funds in the Ministry of Law and Human Rights only to accredited legal aid institution further complicates the procedures of legal aid obtaining, both for the poor and advocate. This government discrimination should be ended by removing the policy and seeking legal aid fund alternatives by exploring the resources available in the community, both private institutions and the having individuals.